Nucleotide sequence and biochemical characterization of the metJ gene from Salmonella typhimurium LT2. - Urbanowski, M L (1985)
The nucleotide sequence of the Salmonella typhimurium metJ gene is presented along with the sequence of the promoter region for the closely linked metB gene. The two genes are transcribed in opposite directions, with transcription initiating from a single promoter for metB, and from two apparent promoters for metJ. RNA polymerase binding sites for metJ and metB, determined by in vitro protection studies, lie adjacent to each other and may overlap. The two metJ promoters, PJ1 and PJ2, are separated by approximately 65 base pairs. Binding of RNA polymerase in vitro could only be observed for PJ1, even though transcripts are initiated from both promoters in vivo. The metJ gene codes for a polypeptide of 105 amino acids with a calculated Mr of 12,110. The translation start site was determined by N-terminal amino acid sequence analysis of a metJ-lacZ fusion protein.